LOWALANGI DALAM KONSEP TRI HITA KARANA DALAM KEARIFAN LOKAL NIAS - Harefa, Darmawan; I Made Sutajaya; I Wayan Suja; Ida Bagus Made Astawa (LPPM Universitas Nias Raya, 2024)
This study aims to explore the local wisdom of the Nias community, particularly the concept of Lowalangi (God) within the context of Tri Hita Karana. This concept emphasizes the balance between humans, nature, and God as a foundation for daily life. Through a literature study method, this research analyzes various sources that link spiritual values, customary practices, and environmental preservation within Nias culture. The findings indicate that Lowalangi serves as a unifying element in social and ecological relationships, creating harmony in the interactions between the community and the environment. This research also highlights the challenges of modernization faced by the Nias community and the importance of education and policies that support the preservation of local wisdom. It is hoped that the results of this study will contribute to a deeper understanding of the integration of local values in efforts towards sustainability and cultural preservation.